One-carbon oxidative annulations of 1,3-enynes by catalytic C–H functionalization and 1,4-rhodium(III) migration - Dooley, Johnathon D.; Lam, Hon Wai (Wiley, 2018)
Rhodium(III)-catalyzed C-H functionalization-oxidative annulations of aromatic substrates with 1,3-enynes that contain allylic hydrogen atoms cis to the alkyne are described. The key step in these reactions is an alkenyl-to-allyl 1,4-rhodium(III) migration to give electrophilic pi-allylrhodium(III) species. Nucleophilic trapping of these species gives heterocycles such as benzopyrans, isobenzofuranones, and isoindolinones.